SUSTAINING KNOWLEDGE TRANSFER ACTIVITIES THROUGH ACHIEVEMENTS IN COLLABORATIVE RESEARCH OUTCOMES - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 1 December 2016 The Knowledge Transfer Programme which was implemented with allocations from the 10th Malaysia Plan has succeeded in producing 459 projects, with the involvement of 1,698 academicians of various knowledge disciplines, 875 graduate interns, 275 industry partners and 184 communities.